2002
DOI: 10.1046/j.1525-1594.2002.06883.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Interdialytic Weight Gain and Acid‐Base Status in Hemodialysis by Bicarbonate

Abstract: The aim of this study was to determine the relationship between interdialytic weight gain and acid-base balance pre- and posthemodialysis in uremic patients undergoing hemodialysis with a high bicarbonate dialysate (39 mmol/L). To this end we studied 8 stable uremic patients on regular hemodialysis thrice weekly who had stable hematocrit values for at least 3 months, similar clinical characteristics including dry weight but widely varying interdialytic weight gain. Arterial line blood samples were collected an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 5 publications
1
12
3
Order By: Relevance
“…This association has also been described recently by Agroyannis et al in 8 stable patients on HD [34]. These findings suggest that the larger nutritional intake, especially proteins, may give rise to a greater generation of acid radicals.…”
Section: Discussionsupporting
confidence: 85%
“…This association has also been described recently by Agroyannis et al in 8 stable patients on HD [34]. These findings suggest that the larger nutritional intake, especially proteins, may give rise to a greater generation of acid radicals.…”
Section: Discussionsupporting
confidence: 85%
“…It has been well recognized that the correction of metabolic acidosis is one of the major goals in hemodialysis treatment of chronic maintenance hemodialysis patients since metabolic acidosis, if left untreated, may lead to systemic detrimental effects such as malnutrition due to negative nitrogen balance and increased protein catabolism, anorexia, fatigue, alterations in bone metabolism and formation, secondary hyperparathyroidism, and decreased cardiovascular functions10). Therefore, the treatment of metabolic acidosis can be assumed to reverse its many side effects in chronic hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Agroyannis et al [79]showed a significant correlation between interdialytic weight gain and the values of prehemodialysis blood pH and bicarbonate, suggesting an important role of the interdialytic weight gain on acid-base equilibrium of uremic patients undergoing hemodialysis. Thus, patients with high interdialytic weight gains may require higher bicarbonate concentrations to achieve normal acid-base status whereas patients with low interdialyic weight gains may require lower bicarbonate concentrations to prevent alkalemia at the end of dialysis.…”
Section: Treatment Of Uremic Acidosismentioning
confidence: 99%